Experiências adversas na infância e saúde mental de crianças de 18 meses e cinco anos em instituição de assistência à primeira infância. - Kedhi, Renata Castro (2018)
Adverse Experiences in Childhood are potential triggers of toxic stress by altering the mechanism of allostasis of the organism that encompass the central nervous system, endocrine system and immune system in formation during gestation and the first years of life. The child submitted to these experiments for a prolonged and continuous time may present alterations in the architecture of the brain with possible repercussions in the long, medium and short term. The general objective of this study is to correlate adverse experiences in childhood and behavioral, emotional and social functioning problems of children from one year and six months to five years of age in an ONG that attends early childhood in Fortaleza - CE. This is a cross-sectional study with a sample of 259 mothers of incomplete children between 18 months and six years old who answered the socioeconomic questionnaire, the Questionnaire on Adverse Experiences in Childhood, and the Childhood Behavior Inventory of 1 ½ to 5 years (CBCL). Exposure to 4 or more experience correlated with changes in total OR behavior: 7.45, 95% CI (2.92 - 19.13), internalizing symptoms OR: 8.78, 95% CI (3.35 - 23,05) and externalizing symptoms OR: 5,12, 95% CI (2,05 - 12,80). The adverse experiences that presented the most behavioral changes were: emotional abuse, physical abuse, emotional neglect, exposure to domestic violence, abuse of substances in the home environment and coexistence with mental illness or suicide. We conclude that adverse experiences experienced by children can cause early changes in their behavior. There is a need for public policies aimed at this age group to promote early intervention and decrease the impact on mental health and behavioral stress behaviors in early childhood. Keywords: Child Development. Adverse Experiences in Childhood. Child Behavior Check List.